PENGARUH PENERAPAN LKS BERBASIS MODEL CREATIVE PROBLEM SOLVING PADA MATERI BUNYI, CAHAYA DAN ALAT OPTIK TERHADAP HASIL BELAJARA IPA SISWA KELAS VIII SMPN 3 PADANG - Riri Camara Putri; Syakbaniah Syakbaniah; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2015)
One causes of  low science  learning is low  of ability  in problems solving. For motivate student increase of ability  in problems solvier needfull ability  in creative  thinking especially for contents of sounds, lighting, and optic instruments.  The purpose of this research was to determine the learning result of the science students and to  investigate  the  effect  student worksheet based models creative problem solving to  the leaning result  of science  students grade VIII at SMPN 3 Padang. Type of research was quasi experimental  research with  randomized  control group only design. The population in this research were the students grade VIII SMPN 3 Padang who were registered in the 2014/2015 academic year.  Sampling  technique was  cluster random sampling. There were  three instruments  in  this  research,  tose are  test  sheet of cognitive domain, observation  sheet of affective domain, and  performance  sheet  of  pschycomotor  domain.  Based  on  the  data  analysis  could  be  presented  the  result  of  this research. Results of  research  show  the average of science  learning outomes are  69,44  and  67,68  at  cognitive  domain,  77,50  and  72,27  at  affective  domain,  84,53  and  78,94  at pschycomotor domain. By using  t analysis,  tcount > ttable  so  alternatif hipotesis  is accepted. The use student worksheet based models creative problem solving  has given significant effect toward Physics studies result of students grade VIII  SMPN 3 Padang at 0,05 significant level